1997
DOI: 10.1002/eji.1830270202
|View full text |Cite
|
Sign up to set email alerts
|

Epitope selection in major histocompatibility complex class I‐mediated pathway is affected by the intracellular localization of an antigen

Abstract: We analyzed the mode of antigen presentation of an endogenous antigen localized in the cytoplasm or in the mitochondria. Pseudomonas aeruginosa PAO leucine-, isoleucine-, valine-binding protein (LIVAT-BP) encoded by the braC gene was used as a model antigen. Using mouse BALB/3T3 cells, we established two LIVAT-BP transfectants by transfection of a plasmid harboring the intact braC or braC gene fused with the mitochondrial transport signal derived from the yeast COXIV gene. One of the resulting transfectants, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Some but no dramatic differences in the cellular origin of the parental proteins were apparent. It was remarkable that a number of proteasomeindependent ligands arose from mitochondrial proteins of the respiratory chain, raising the interesting possibility of a putative mitochondrial processing of these ligands, in line with previous speculations (68) and with the finding that the same protein expressed in the cytosol or in the mitochondria produced different MHC class I-restricted peptide epitopes (69). In addition, proteasome-independent ligands derived from internal sequences of secreted proteins were not found.…”
Section: Discussionsupporting
confidence: 62%
“…Some but no dramatic differences in the cellular origin of the parental proteins were apparent. It was remarkable that a number of proteasomeindependent ligands arose from mitochondrial proteins of the respiratory chain, raising the interesting possibility of a putative mitochondrial processing of these ligands, in line with previous speculations (68) and with the finding that the same protein expressed in the cytosol or in the mitochondria produced different MHC class I-restricted peptide epitopes (69). In addition, proteasome-independent ligands derived from internal sequences of secreted proteins were not found.…”
Section: Discussionsupporting
confidence: 62%
“…Processing of antigen in mitochondria and in the cytosol has been shown to generate different repertoires of antigenic epitopes; this was demonstrated using cells that express a bacterial protein either in mitochondria or in the cytoplasm [26]. Furthermore, human CTL recognize epitopes of the EBV-derived nuclear antigen EBNA1 that are apparently processed only in the alternative pathway: human CD8 + CTL lines recognize EBNA1 epitopes in the context of HLA-B35.01 or HLA-A2.03 on cells when the nuclear antigen is supplied as an exogenous antigen but not when the targets express endogenous EBNA1 [27].…”
Section: Distinct Ctl-stimulating Epitope Repertoiresmentioning
confidence: 98%
“…In contrast, DNGR-1, which was previously shown to be involved in the cross-presentation of cellassociated antigens (37), appeared not to be involved in the crosspresentation of mitochondrial OVA. Previous papers have provided insights into the mechanisms by which mitochondrial-derived proteins may intersect the antigen processing and presentation pathway (15,16). However, these papers fail to demonstrate whether mitochondrial antigenic proteins can be efficiently taken up by DCs in vivo and cross-presented to antigen-specific CD8 þ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Yamazaki and colleagues have demonstrated that cytoplasmic versus mitochondrial localization of antigenic protein LIVAT-BP determines which portions of the protein are selected as antigenic epitopes for CD8 þ T-cell recognition (16). Although these results are of interest, this paper falls short of distinguishing whether antigen location modulates: (i) in vivo cross-priming of T-cell responses; (ii) proteasome-dependent degradation of the antigenic protein; and (iii) tumor growth.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation